ANTIDEPRESSANT ACTIVITY OF ETHANOLIC EXTRACT OF NYMPHAEA ALBA FLOWER IN ALBINO MICE - MADHAVI EERIKE; UMA MAHESWARI .N (International Journal of Pharma and Bio Sciences, 2013)
The present study was undertaken to evaluate the anti-depressant activity of Nymphaea Alba Flower (NAF) in albino mice. Forty eight adult albino mice (Swiss strain) weighing between 25-35gr were chosen. 24 animals were assigned to forced swim test (FST) and 24 o tail suspension test (TST).In each model there were 4 groups. The control group received vehicle (10 ml /kg-1, p.o.), the two test groups received ethanolic extract of Nymphaea Alba Flower 100, 200 mg kg-1 and the standard, imipramine (10 mg /kg-1, p.o.) p.o., respectively, 60 minutes prior to the acute study. In chronic study, the drugs were given orally once a day for 10 days and the last dose was given 60 minutes before the experiment. Duration of immobility was noted in FST and TST. Statistical analysis was performed using Mean±SEM and ANOVA followed by Dunnett’s test. The p<0.05 was considered statistically significant. Ethanolic extract of Nymphaea Alba Flower produced significant antidepressant effect at both the doses (100, 200 mg kg-1), as indicated by reduction in the duration of immobility compared to the control. The antidepressant effect was higher at 200mg than at 100 mg. In addition, the effect at 200 mg was greater than that of imipramine. Ethanolic extract of Nymphaea Alba Flower thus has shown significant antidepressant activity greater than imipramine in mice.